Caries status among 6-year-old children born with cleft lip and palate in Norway: a nationwide study - Osman, O. E.; Yassin, M. A.; Bjering, R.; Saele, P. K.; Korsnes, I. M. T.; Hagbø, M. O. B.; Sivertsen, Å.; Lie, S. A. (Frontiers in Oral Health, 2025)
BackgroundOrofacial cleft (OFC) is the most common congenital malformation affecting the craniofacial area. A major challenge in managing children with OFC is their increased susceptibility to dental caries. This study aims to explore the association between dental caries and various potential variables, including OFC types, sex, and the presence of additional congenital deformities.MethodsThis study includes 6-year-old children with OFC registered in the Norwegian Registry of Cleft Lip and Palate. Children were classified into two main groups: cleft lip and/or palate (CL ± P)—including cleft lip only (CLO) and cleft lip and palate (CLP)—and cleft palate only (CPO). The association between dental caries and OFC types, sex, and additional congenital deformities was analyzed using chi-square tests and logistic regression, reporting p-values and odds ratios (OR) with 95% confidence intervals (CI).ResultsAmong 551 children with OFC (343 boys and 208 girls), 37% had CLP, 36% had CPO, and 27% had CLO. Dental caries experience was found among 99 (18%) children (66 males and 33 females): 39 had CPO, 37 had CLP, and 23 had CLO. No association between dental caries and OFC type was found (p = 0.627). However, a significant association was found between dental caries and the presence of additional congenital deformities (OR = 2.10, 95% CI: 1.30–3.39, p = 0.002).ConclusionBoys are more commonly affected by OFC than girls. Children with OFC and additional congenital deformities are more susceptible to caries, indicating the need for more targeted and individualized preventive oral health strategies.